Secret Passages : the Theory and Technique of Interpsychic Relations. (Taylor & Francis, 2010)
Secret Passages provides a theoretical and clinical exploration of the field of psychoanalysis. It looks at the pivotal relationship between analyst and client and its importance to the psychoanalytic process. Offering a uniquely global perspective, Bolognini considers the different trends in contemporary psychoanalysis, charting a course between the innovative and traditional. Divided into three parts, areas of discussion include:plurality and complexity in the internal worldthe complex nature of psychoanalytic empathyfrom the transpsychic t.